MASA DEPAN DAN MANFAAT NEKROPOLIS GILIMANUK, SEBUAH KONTEMPLASI ARKEOLOGI. - Sutaba, I Made (Kebudayaan, 2018)
AbstractUntil the present days, archaeological research in Indonesia and prehistoric research particularly in Bali, have discovered an important and remarkable cultural heritage, among them, there are prehistoric sites and artefacts that informed about the prehistoric life in Bali. Based on the result of this research, it is known that the necropolis and the prehistoric burial site of Gilimanuk are spectacular and potential culture heritages. The problem in this research is to know, how is the future and benefits of the necropolis sites and the prehistoric Gilimanuk grave site for the development of Indonesian nationâ??s character? The purpose of this study is to explain the benefits of the existence of these sites for the development of national character. Learning this problems, the objectives of this research is to find out the answer of the problems. To reach this objectives, this research is planned step by step. The method that used for collecting data including field observation with interview and literature study. The next step, analysis was carried out by method of typological analysis, contextual analysis, functional analysis and comparative study. The results of this study indicate two items. First, archeologically, the necropolis site and the prehistoric Gilimanuk grave site are very important as a cultural force containing socio-cultural values that lived 2000 years ago. Secondly, the site can provide enormous benefits for the development of national cultural resilience, national character, and dynamic spirit of nationalism.AbstrakSampai sekarang, penelitian arkeologi di Indonesia dan penelitian prasejarah di Bali telah menemukan warisan budaya yang penting dan menarik. Di antara temuan ini, adalah situs dan artefak prasejarah yang menggambarkan kehidupan masyarakat prasejarah Bali. Berdasarkan hasil-hasil penelitian selama ini dapat diketahui, bahwa situs nekropolis dan situs kuburan prasejarah Gilimanuk adalah warisan budaya yang spektakuler dan potensial. Permasalahannya adalah, bagaimana masa depan dan manfaat situs necropolis dan situs kuburan prasejarah Gilimanuk tersebut bagi pembangunan karakter bangsa kita? Tujuan dari penelitian ini adalah memaparkan manfaat keberadaan situs-situs tersebut untuk pembangunan karakter bangsa. Untuk mencapai tujuan ini, maka penelitian ini direncanakan secara bertahap, mulai dengan pengumpulan data dengan metode kajian pustaka, observasi lapangan, pencatatan, pendokumentasian, dan wawancara. Langkah berikutnya adalah analisis dengan metode analisis tipologis, analisis kontekstual dan studi perbandingan. Hasil penelitian ini menunjukkan bahwa, pertama secara arkeologis, situs nekropolis dan situs kuburan prasejarah Gilimanuk sangat penting sebagai kekuatan budaya yang mengandung nilai-nilai sosial-budaya yang hidup 2000 tahun yang silam. Kedua, situs tersebut dapat memberikan manfaat yang sangat besar bagi pembangunan ketahanan budaya bangsa, karakter bangsa, dan semangat nasionalisme yang dinamis.